Precaution, threshold risk and public deliberation - Holm, Sune; Wareham, Christopher (2019)
It has been argued that the precautionary principle is incoherent and thus useless as a guide for regulatory policy. In a recent paper in Bioethics, Wareham and Nardini propose a response to the ‘precautionary paradox’ according to which the precautionary principle's usefulness for decision making in policy and regulation contexts can be justified by appeal to a probability threshold discriminating between negligible and non-negligible risks. It would be of great significance to debates about risk and precaution if there were a sound method for determining a minimum probability threshold of negligible risk. This is what Wareham and Nardini aim to do. The novelty of their approach is that they suggest that such a threshold should be determined by a method of public deliberation. In this article I discuss the merits of Wareham and Nardini’s public deliberation method for determining thresholds. I raise an epistemic worry about the public deliberation method they suggest, and argue that their proposal is inadequate due to a hidden assumption that the acceptability of a risk can be completely analysed in terms of its probability.
Keywords: Ethics; Precautionary Principle; precautionary regulation; public deliberation; Risk